FATAL CANINE PARVOVIRUS INFECTION WITH SECONDARY BACTERIAL AND PARASITIC COMPLICATIONS IN A PUPPY: A CASE REPORT - Egrina Sonta Bako; I Putu Cahyadi Putra; Ida Bagus Oka Winaya; I Gusti Ngurah Kade Mahardika; I Nengah Kerta Besung (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Canine parvovirus (CPV) is a highly infectious viral disease that poses a significant threat to puppies, often resulting in fatality if not diagnosed and treated promptly. This report investigates the cause of death of a nearly two-month-old puppy in Denpasar City. Diagnosis was confirmed through a comprehensive approach, including a thorough history, clinical examination, hematology, anatomical pathology, histopathology with hematoxylin and eosin (H&E) staining, polymerase chain reaction (PCR) for CPV, bacteriology, and parasitology examinations. Anamnesis revealed that the two puppies succumbed after exhibiting symptoms such as anorexia, vomiting, bloody diarrhea, dehydration, and cachexia, which were also observed in this puppy. Necropsy findings indicated multiorgan lesions, including hemorrhage, congestion, hyperemia, uneven organ discoloration, swelling of the heart and spleen, and worm infestation in the stomach. Histopathological analysis revealed multi-organ inflammation characterized by hemorrhage, necrosis, edema, and inflammatory cell infiltration in all organs, with lesions typical of CPV, including lymphoid follicular necrosis and intestinal Lieberkühn crypts in the intestine. PCR confirmed CPV infection, as evidenced by a 900 bp DNA band. Bacteriological examination revealed the presence of Escherichia coli and Streptococcus spp. in the intestine and Staphylococcus spp. in the spleen. Parasitological examination revealed the presence of adult worms, larvae, and eggs of Toxocara canis in the fecal sample. Based on these findings, the death of the puppy was attributed to CPV infection compounded by secondary bacterial and parasitic infections. Further testing is recommended to ascertain potential co-infection with Canine Distemper Virus.